Cross-Linguistic Influences in the Simultaneous Learning of French and English Among Algerian Primary School Third Graders - Tobbi, Saida (Studies in Teaching and Education, 2025)
Multilingual reforms increasingly place young learners in classrooms where two new languages are taught side by side. Yet little is known about how such contexts shape cross-linguistic influence (CLI) at the very start of formal instruction. This study examines Algerian Grade 3 pupils’ simultaneous acquisition of French and English following the 2022 reform that introduced English alongside French in primary schools. A mixed-methods design combined diagnostic tests with 372 pupils, questionnaires with 48 teachers, and interviews with 60 parents to capture both transfer patterns and the conditions in which they arise. The findings show that CLI is systematic rather than random. Pupils consistently defaulted to French, producing predictable lexical (32%), phonological (28%), and orthographic (22%) transfers. These patterns reflected structural overlap between the languages but were also reinforced by French’s entrenched dominance in Algerian education. Teachers frequently relied on French to scaffold instruction, while parents, lacking English competence, provided support mainly in French. The study advances theory by showing that CLI is not only cognitive but also socially conditioned. Pedagogically, it highlights the need for teacher training in multilingual methods and contrastive pedagogy, while at the policy level it underlines that symbolic promotion of English requires sustained investment in resources and teacher development.